2018
DOI: 10.14740/jocmr3362w
|View full text |Cite
|
Sign up to set email alerts
|

An Improvement of Cardiovascular Risk Factors by Omega-3 Polyunsaturated Fatty Acids

Abstract: An epidemiological survey in the Northwest Greenland reported that the Greenlanders have a lower frequency of acute myocardial infarction and diabetes mellitus. The very low incidence of ischemic heart disease in the Greenlanders was explained by consumption of a diet rich in omega-3 polyunsaturated fatty acids (PUFAs). Possible anti-atherothrombotic effects of omega-3 PUFA include an improvement of lipid metabolism such as a reduction of triglyceride and an increase of high-density lipoprotein-cholesterol (HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 58 publications
3
33
0
4
Order By: Relevance
“…This result indicates that the effect of n-3 PUFA on HDL-C varies by the difference of clinical backgrounds of studied patients. Our recent study reported that DHA induces a greater increase of HDL-C as compared with eicosapentaenoic acid (EPA) [28], supporting our previous study.…”
Section: Discussionsupporting
confidence: 87%
“…This result indicates that the effect of n-3 PUFA on HDL-C varies by the difference of clinical backgrounds of studied patients. Our recent study reported that DHA induces a greater increase of HDL-C as compared with eicosapentaenoic acid (EPA) [28], supporting our previous study.…”
Section: Discussionsupporting
confidence: 87%
“…Natural products from marine and freshwater microalgae have been widely studied in the last years highlighting their diversified activities, such as antioxidant, antibacterial, antitumor, anti-inflammatory, anti-hypertensive, cardioprotective, and antidiabetic [126,127]. In addition, various studies have used an OSMAC approach in order to increase the production of specific metabolites [5,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…(AGPI LC n-3), présents naturellement dans les aliments d'origine marine comme les poissons gras (tableau 1), peuvent modifier les propriétés physicochimiques des membranes [11][12][13][14] et pourraient donc interférer avec les effets de ces toxiques chimiques. Ces AGPI LC n-3 sont d'ailleurs décrits pour la prévention ou le traitement de nombreuses pathologies [15][16][17] telles que les maladies cardiovasculaires [18][19][20][21], inflammatoires [22,23] et les cancers [24,25].…”
Section: Mots-clefsunclassified